Detecting Passive Radar Reflectors for Automotive Applications - Autioniemi, Matti; Händel, Chris; Saarenpää, Timo (Lapin ammattikorkeakoulu, 2019)
This report has been developed in the Arctic Challenge research project. The Arctic Challenge research project is funded by the Finnish Transport Agency (FTA) and the Finnish Transport Safety Agency (TraFi). The project is part of the Aurora intelligent road project of the Finnish Transport Agency and the NordicWay2 project funded by the Connecting Europe Facility of the European Union. The testing weeks for the research project will take place on the 10-km-long test stretch of the Aurora Vt21 (E8) intelligent road section in the years 2017–2019. Furthermore, the project is part of the Traffic Lab cooperation. The contracting partners involved in the research project include Dynniq Finland Oy, Indagon Oy, Infotripla Oy, Lapland University of Applied Sciences Oy, Roadscanners Oy, Sensible 4 Oy and VTT Technical Research Centre of Finland Oy. The main author of this report was Dr. Chris Händel from Roadscanners Oy. The contributors from Lapland University of Applied Sciences have been Mr. Heikki Konttaniemi and Mr. Matti Autioniemi. Project engineers Mr. Matti Autioniemi, Mr. Jori-Jaakko Niskanen, Mr. Kari Moilanen from Lapland UAS have performed practical field-testing and developed test equipment with the help of Ward Martens, a thesis student, from PLX University College in Belgium, together with Dr. Händel. The project has been technically steered by Dr. Timo Saarenketo, Mr. Pekka Maijala and Mr. Timo Saarenpää from Roadscanners Oy. Authors would also like to acknowledge Ilkka Kotilainen, Reija Viinanen and Alina Koskela from the Finnish Transport Agency, and Anna Schirokoff from the Finnish Transport Safety Agency, for their valuable help and support and steering of the project. Note: Arctic Challenge promotes open data policy. Data from Arctic Challenge tests is made available for third parties